Conceptualizing and measuring distance in international business research: Recurring questions and best practice guidelines - Beugelsdijk, Sjoerd; Ambos, Björn; Nell, Phillip C (Journal of International Business Studies, 2018)
Distance is a central concept in international business research, yet there is debate about the construct as well as its operationalization. In this editorial, we address three of the most important recurring questions posed by authors, editors, and reviewers by examining the theory, methods, and data of distance research. We discuss (1) how to theorize on distance, and (2) what method and (3) what data to use when constructing a distance index. We develop practical recommendations grounded in theory, illustrating and supporting them by calculating cross-country distance indices for all available country pairs and two of the most used distance indices: cultural and institutional. We show that, whereas a specific method to calculate distance may matter to some extent, the choice for a specific cultural or institutional framework to measure cultural or institutional distance has a major impact on country–pair distances. Overall, this editorial highlights the importance of matching data and method to the theoretical argument.